2023
DOI: 10.3390/ijms241914508
|View full text |Cite
|
Sign up to set email alerts
|

SAM/SAH Mediates Parental Folate Deficiency-Induced Neural Cell Apoptosis in Neonatal Rat Offspring: The Expression of Bcl-2, Bax, and Caspase-3

Qinghan Ren,
Guoquan Zhang,
Ruiting Yan
et al.

Abstract: Research demonstrated that folate deficiency in either the mother or father could impact the biological functions of the offspring’s of neural cells. Folate deficiency can also impair the methionine cycle, thus contributing to the conversion of S-adenosylmethionine (SAM) to S-adenosylhomocysteine (SAH), which could potentially cause damage to the central nervous system. The study focused on the effect of parental folate deficiency on neural cell apoptosis in offspring neonatal rats and whether it is mediated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(50 reference statements)
0
0
0
Order By: Relevance
“…Bax and Bcl-2, which belong to the Bcl-2 protein family, play an important role in the regulation of cell apoptosis, while caspases participate in regulation of apoptotic cell death [82][83][84]. Previous investigators have reported that apigenin is able to attenuate the hepatic apoptosis by decreasing the expression of Bax and caspase-3 and increasing the expression of Bcl-2 in rats [85].…”
Section: Discussionmentioning
confidence: 99%
“…Bax and Bcl-2, which belong to the Bcl-2 protein family, play an important role in the regulation of cell apoptosis, while caspases participate in regulation of apoptotic cell death [82][83][84]. Previous investigators have reported that apigenin is able to attenuate the hepatic apoptosis by decreasing the expression of Bax and caspase-3 and increasing the expression of Bcl-2 in rats [85].…”
Section: Discussionmentioning
confidence: 99%